Tithes in Huamanga - Huertas, Lorenzo (1982)
The tithe: "part of the fruits that the faithful pay to the church of God, which is regularly a tenth" or tenth of the fruits that are harvested, although sometimes less depending on the case and custom of the places". To these definitions we can add that the tithe was a form of coercive taxation paid by the owners of "decimal lands"; failure to comply implied major excommunication late sentisa ipso facto. When this penalty was applied, the name of the excommunicated person was put on the door "of the churches of where they were parishioners and he did not order them to absolve or remove them from the tablet until they have fulfilled the payment".